Pemeliharaan Arsip Dinamis Aktif di SMA IBA Palembang - Syabrina, Dea; Niswah, Choirun; Ibrahim, Ibrahim (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the active dynamic records maintenance system implemented at SMA IBA Palembang. The research is qualitative in nature with a descriptive qualitative approach. Data were collected through interviews, observation, and document analysis. The study involved 12 informants selected using purposive sampling, where the researcher chose samples based on specific considerations or characteristics relevant to the research objectives. The findings indicate that although SMA IBA Palembang has an adequate records management system, several challenges remain, including limited storage space, lack of staff training, and minimal use of information technology in records management. To improve the maintenance of active dynamic records in the future, the school needs to enhance storage facilities, provide regular training for staff, and utilize digital technology to streamline the records management process